INTEGRASI MEDIA HILOY KARTU EKOSISTEM BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN HASIL BELAJAR DAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Evi Shafri Mustika Nebo; Aisyah Ali; Tiffany Shahnaz Rusli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the learning outcomes of science ecosystem materials and cultural literacy of elementary school students through the Hiloy Ecosystem Card media based on Sentani local wisdom. The research used the Kemmis and McTaggart model Class Action Research (PTK) design (Kemmis & McTaggart, 1988) which was carried out in two cycles. The subject of the study is a grade V student of SD Muhammadiyah Abepura. Learning outcome data was collected through pre-action tests, cycle I, and cycle II, while cultural literacy was measured using cultural literacy behavior observation sheets during learning. The results showed that the average score increased from 56.9 in pre-action to 72.1 in cycle I and 82.9 in cycle II. Learning completeness increased from 42.9% to 66.7% and reached 85.7% in cycle II. The N-gain value of the class was 0.60 (Hake, 1998) (medium-high category). Cultural literacy observations showed an average total score of 40.96 (Good category), with the distribution of categories: Very Good (2 students), Good (14 students), and Fair (11 students). These findings indicate that Hiloy Kartu Ecosystem's media is effective as a contextual learning strategy that integrates science concepts with local cultures to enhance students' understanding and build cultural-ecological awareness.